المكونات المادية للمسجد وأثرها التفاعلي - مهنديس, عدنان (University of Eloued جامعة الوادي, 2019)
ملخص المقال باللغة العربية: تتعدد المكونات المادية في مؤسسة المسجد وتنقسم باختلاف حجم وظيفتها في النشاط المسجدي وكذا حجم تاثيرها في التفاعل المسجدي المرصود، ويمكن تقسيمها الى مكونات أساسية ومكونات ثانوية. ولعل من اهم هذه المكونات المادية: *المحراب وما يحتمله المكون من دلالات لغوية وتاريخية يمكن من خلالها أن يتم التأطير التفاعلي لهذا العنصر. *الصومعة وما تحظى به من أهمية تواصلية متعددة الأبعاد بما يحقق حاجة ومصلحة المجتمع. *المقصورة وما تقدمه من خدمات وظيفية تغذي الحاجة التواصلية لمؤسسة المسجد ورواده. *المنبر ورسالته الكبرى في توجيه التفاعلات المسجدية وتسديدها نحو الخير والصلاح. *الزخارف المسجدية وما يكتنفها من نقاش تفاعلي في الشق التواصلي الجمالي سواء موافقة أو معارضة. • ملخص المقال باللغة الانجليزية: The materialistic components of the mosque and their interactive effect The mosque, as an institution, features various materialistic components. Each component can be classified or divided according to the degree of its function within the mosque's activities and the degree of its influence on targeted interactive goal . These materialistic components can be primary or secondary. The most important primary components are the following: *"Almihrab": (a niche in the wall where the imam performs the prayer) Its linguistic and historical significance can be a channel for framing interaction. *The minaret. This well_ regarded tower and its multidimensional interactive importance can help in satisfying society's needs and interest. *Maqsurah: The functional services this component offers nurture the communicative needs for the institution of the mosque and its visitors. *Alminbar. This puplit where the orator stands has a great message to convey: Guiding all forms of interaction in the mosque and targeting it towards goodness and rightness. *Almasjid's decorations: from an aesthetically communicative perspective, one can see that these artistic decorations trigger a for_ or_ against interactive discussion.
مقال
Keywords: مك ; مادية ; مسجد ; أثر ; التفاعلي